Assessing the Responsiveness of Public Service Delivery at the Class IIA State Detention Facility in Ambon - Orpha Riupassa; Ignasius Setitit; Ferdinand C. Renyut (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Abstract This study aims to evaluate the level of public service responsiveness at the Class IIA State Detention Center (Rutan) in Ambon by examining five key aspects: speed, accuracy, satisfaction, precision, and accessibility of services. Responsiveness is a crucial indicator in assessing how well public services meet the needs and expectations of inmates and external stakeholders in an effective and efficient manner. The research was conducted at the Class IIA Detention Center in Ambon from February to April 2025. A descriptive qualitative approach was employed, with data collected through in-depth interviews with officers and inmates, direct observation of service processes, and a review of relevant administrative documents and internal policies. The data were analyzed using the interactive model, which consists of three stages: data reduction, data display, and conclusion drawing. The findings reveal that service responsiveness still faces several challenges. Officers are not yet able to fully respond to inmates’ requests quickly and in a timely manner, leading to delays in meeting their needs. While some inmates expressed satisfaction, complaints persist regarding limited facilities and long waiting times. Inaccuracies in the delivery of information and service execution continue to affect the overall quality of service. Additionally, access to services remains inadequate, particularly for external stakeholders. This study recommends optimizing digital-based service systems, enhancing the capacity and competence of service personnel, and strengthening supervision of service procedures. These efforts are expected to improve the quality of public services to be more responsive, accurate, and aligned with the needs of service users.